Legislative Capacity and Credit Risk. Issue 3 (6th June 2018) - Fortunato, David; Turner, Ian R.
Abstract: Legislatures differ in their institutional capacity to draft and enact policy. While strong legislatures can increase the congruence of policy outcomes to the electorate's preferences, they can also inject uncertainty into markets with their ability to alter the political economic landscape. We argue that this uncertainty will manifest in a state's ability to borrow and hypothesize a negative relationship between legislative capacity and creditworthiness. Using ratings of general obligation bonds issued by the American states over nearly two decades and data on the institutional capacity of state legislative assemblies, we find support for the claim that having a legislature that is better equipped to affect policy change increases credit risk evaluations. The results we present broaden our understanding of the importance of legislative institutions, the determinants of credit risk, and the economic implications of democratic responsiveness.